2023
DOI: 10.2478/rtuect-2023-0050
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impact of Latvian New Common Agriculture Policy: Transition to Climate Neutrality

Lelde Vistarte,
Jelena Pubule,
Lauma Balode
et al.

Abstract: Agriculture ranks among the key sectors responsible for substantially rising greenhouse gas (GHG) emissions. The increase in emissions contributes to the adverse effects of climate change, including threats to biodiversity, the potential for extreme weather events, elevated sea levels, and alterations to ocean currents. The European Union’s Common Agricultural Policy (CAP) is a comprehensive framework that aims to achieve sustainability and advance the agricultural sector’s journey towards climate neutrality b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The study by L. Vistarte et al (2023) shows a significant positive impact of the new common agricultural policy of Latvia on the climate resilience of the sector. The authors found that Latvia's new policy aimed at climate neutrality was successful.…”
Section: Acknowledgementsmentioning
confidence: 97%
“…The study by L. Vistarte et al (2023) shows a significant positive impact of the new common agricultural policy of Latvia on the climate resilience of the sector. The authors found that Latvia's new policy aimed at climate neutrality was successful.…”
Section: Acknowledgementsmentioning
confidence: 97%
“…Sample fragment of CORINE Land Cover maps (same scale)By closing the gap between current and potential diversity, crop diversity could double on 84% of the world's agricultural land without changing the total amount of food produced globally(Merlos & Hijmans, 2022), and this would improve the quality and value of ecosystem services provided(Sujetovienė & Dabašinskas, 2023). The Common Agricultural Policy and the European Green Deal strategy play an important role in this respect, improving the biodiversity of the agricultural landscape through various financial incentives(Vistarte et al, 2023). In addition to its environmental benefits, crop diversification brings positive economic and social effects such as increased exports and new jobs(Neogi & Ghosh, 2022).…”
mentioning
confidence: 99%